The Relationship Between The Use Of Youtube Media And The Learning Outcomes Of Students At SMKN 6 Padang. - Dolla, Resti Tri; Zulfikar, Dikki; Yulastri, Asmar; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research aims to: 1) Analyzing how the use of Youtube media in SMKN 6 Padang, 2) Analyzing how the learning outcomes of students in class Xl Pasrty and Bakery subjects at SMKN 6 Padang, 3) Analyzing the relationship between the use of YouTube media on the learning outcomes of students in class Xl Pastry and Bakery subjects at SMKN 6 Padang. This type of research is quantitative research with a correlational approach. The population in this study were Xl culinary class students with 101 people. The research sample amounted to 50 people with the sampling technique was simple random sampling. The data collection technique was carried out using a questionnaire (questionnaire) using a Likert scale that had been tested for validity and reliability. Data analysis using descriptive analysis. The results showed that: 1) The use of Youtube media is in the moderate category (73.25%), 2) Student learning outcomes are in the moderate category (78.78%), 3) Based on the results of the research analysis, the correlation value rxy 0.603 was obtained and the tcount value (5.242)> t table 1.667. So it can be said that there is a positive relationship between the use of YouTube media and student learning outcomes.